Effect of soil moisture stress on growth light azimuth and yield of dryland sorghum (MAUSAM, 1993)
Based on weekly data for 4 years (1986-1989) at Bellary, soil moisture balance for rabi sorghum has been worked out for both irrigated and non-irrigated conditions. These soil moisture values have been used to identify periods of water stress which the crop experienced. during the growth cycle. The extent of yield reduction due to the stress was then evaluated from the actual soil water content and total available water extent and discussed. The ratio of evapotranspiration to potential evapotranspiration and water requirement of the crop has also been worked out to assess the stress situation of the crop during its growing period. This ratio has been found to be related to moisture availability at the root zone.